2005
DOI: 10.1161/circulationaha.104.483628
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Aortic Pulse Wave Velocity, a Marker of Arterial Stiffness, Predicts Cardiovascular Events in Well-Functioning Older Adults

Abstract: MD; for the Health ABC StudyBackground-Aging results in vascular stiffening and an increase in the velocity of the pressure wave as it travels down the aorta. Increased aortic pulse wave velocity (aPWV) has been associated with mortality in clinical but not general populations. The objective of this investigation was to determine whether aPWV is associated with total and cardiovascular (CV) mortality and CV events in a community-dwelling sample of older adults. Methods and Results-aPWV was measured at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
796
3
50

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,120 publications
(871 citation statements)
references
References 60 publications
22
796
3
50
Order By: Relevance
“…In aortic PWV studies, MI was often included in the definition of outcome variables such as overall CVD events or CHD, but not investigated as an individual outcome as has been done in this study. These previous studies show an association between aortic PWV and CHD,8, 31, 32, 33 as is shown here as well. Our results are consistent with previous PP studies that reported associations with both incident MI3 and CHD34 after adjustment for traditional CVD risk factors in a hypertensive and community‐based cohort, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In aortic PWV studies, MI was often included in the definition of outcome variables such as overall CVD events or CHD, but not investigated as an individual outcome as has been done in this study. These previous studies show an association between aortic PWV and CHD,8, 31, 32, 33 as is shown here as well. Our results are consistent with previous PP studies that reported associations with both incident MI3 and CHD34 after adjustment for traditional CVD risk factors in a hypertensive and community‐based cohort, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The association between aortic PWV with HF is inconsistent across studies 32, 35. We found an association between ASI and HF after adjustment for traditional CVD risk factor but it had little discriminating power.…”
Section: Discussioncontrasting
confidence: 62%
“…Increased stiffening of the large elastic arteries occurs with advancing age and is a major independent risk factor for age‐associated CV events and clinical CVD (Reddy et al ., 2003; Sutton‐Tyrrell et al ., 2005; Fleenor et al ., 2012b). Increased aortic stiffness, in particular, reduces the ability to buffer increases in pressure produced by systolic ejection of blood into the large elastic arteries with each cardiac contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have performed only one PWV measurement as it is not otherwise stated. 1,3,[17][18][19][20][21][22][23][24][25][26][27][28] One study reported that one PWV measurement was performed 29 and two studies 30,31 referred that two and three PWV measurements were performed, respectively, and an average value was then calculated. Thus, based on the results of this study, a substantial variation (and 'bias') in the determined CVR and the calculated statistical measures may exist, which depends on the number of PWV measurements.…”
Section: Discussionmentioning
confidence: 99%